Workplace Spirituality and Employee Attitudes: Moderating Role of Organizational Politics (Journal of Business and Management Research, 2017)
There is growing interest in examining the influence of workplace spirituality (WPS) on employee attitudes. However, there is still lack of studies that examine the relationships between WPS and employee attitudes and moderating effect of other variables on these relationships. This study examined the relationships between WPS and two job attitude variables – job satisfaction and job involvement. It also examined the moderating effect of perceptions of organizational politics (POP) on these relationships. Survey questionnaire was used to collect data from 500 employees working in two Nepali organizations, of which 480 questionnaires were used for further analysis. Structural equation modeling and multiple moderated regression analyses were used to test the hypothesized relationships. Results indicated that WPS is significantly positively related to job satisfaction and job involvement and POP moderates the relationship between WPS and job involvement. Research implications are discussed and limitations of the study are highlighted.